Insulin receptor substrate-1 gene mutations in NIDDM; implications for the study of polygenic disease - Hitman, G A; Hawrami, K; McCarthy, M I; Viswanathan, M; Snehalatha, C; Ramachandran, A; Tuomilehto, J; Tuomilehto-Wolf, E; Nissinen, A; Pedersen, O (Diabetologia, 1995)
Variations in the coding regions of the insulin receptor substrate-1 (IRS-1) gene have recently been suggested to contribute to the susceptibility of non-insulin-dependent diabetes mellitus (NIDDM). The purpose of this study was to examine the role of the IRS-1 missense mutations at codons 972 (glycine to arginine) and 513 (alanine to proline) in two diverse populations from South India and Finland at high risk for NIDDM. DNA was amplified and digested with restriction enzymes BstN1 to detect the codon 972 mutation and Dra III to detect the codon 513 mutation. The codon 513 mutation was not found in the study subjects. The codon 972 mutation was present in 10.3% of 126 middle-aged NIDDM subjects and 5.3% of 95 matched control subjects in the South Indians (p = 0.17). In elderly Finnish subjects the frequency of the mutation was 7.5% in 40 NIDDM subjects and 7% in 42 matched control subjects. The frequency of codon 972 mutation in the South Indian NIDDM subjects was very similar to the two previously published studies in Danish and French subjects although each study individually fails to reach conventional levels of significance. The data from all four ethnic groups were analysed together after ascertaining that significant heterogeneity did not exist between the studies. Overall, the frequency of the codon 972 mutation is found in 10.7% NIDDM subjects and 5.8% control subjects (p = 0.02). These studies suggest that the codon 972 mutation of the IRS-1 gene might act as a susceptibility gene predisposing to NIDDM in certain ethnic groups.